2016
DOI: 10.1016/j.apr.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Screening of short-lived climate pollutants in a street canyon in a mid-sized city in Brazil

Abstract: a b s t r a c tBlack carbon (BC) and tropospheric ozone (O 3 ) are two main short-lived climate pollutants also linked to health effects. They are ubiquitous in street canyons, since this environment is a hotspot for trafficrelated pollutants due to their particular airflow characteristics, location within the cities and the high density of vehicles and population.We report on BC and O 3 concentrations measured in a Brazilian city in November 2014. Measurements of BC at 880 nm wavelength were conducted in a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 45 publications
1
9
0
1
Order By: Relevance
“…O 3 concentration simulated in Pinheiros and Paulista Avenue is less than background concentrations, these same results are reported by Wu et al (2019). As noted in Krecl et al (2016), this behavior is caused by the high NO X emissions inside the street urban canyons, which rapidly deplete the formed O 3 and the one from the rooftop (i.e, background concentration).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…O 3 concentration simulated in Pinheiros and Paulista Avenue is less than background concentrations, these same results are reported by Wu et al (2019). As noted in Krecl et al (2016), this behavior is caused by the high NO X emissions inside the street urban canyons, which rapidly deplete the formed O 3 and the one from the rooftop (i.e, background concentration).…”
Section: Discussionmentioning
confidence: 93%
“…In Brazil, previous studies of air quality in urban canyons dealt with measurements of black carbon and O 3 inside a street canyon in Londrinas city center (Krecl et al, 2016), and dispersion of NO x was simulated in Curitiba with the ENVI-met model (Kruger et al, 2011). To our knowledge, this is the first study of modeling O 3 and NO x inside street urban canyons in Sao Paulo Metropolitan Area (SPMA) where it is very often the exceedance of O 3 state air quality standard (Andrade et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…C5 has an outstanding secondary nocturnal O3 peak and the smallest diurnal range. Krecl et al (2016) also observed a secondary O3 maximum at night in Londrina (a site within C5), which they attributed to horizontal and vertical transport of O3 from other regions.…”
Section: O3 Data Reduction Based On Cluster Analysismentioning
confidence: 85%
“…Boian and Andrade (2012) conducted a study using a photochemical model and pinpointed that a nocturnal O3 peak of 176 g/m 3 (at 22:00 h) in Campinas (northwest of the city of São Paulo) was due to a plume from the MASP, Londrina (both within C5) are easterly and easterly/southeasterly, respectively. More precisely,Krecl et al (2016) observed easterly components in Londrina between 00:00 and 10:00 h.C3 is the cleanest cluster and although Santos and Cubatão have a relatively large fleet (a combined total of 331,600 vehicles) and Cubatão is an industrial city with a cluster of petrochemical, steel and fertilizer industries, they are located on the coast, where frequent overcast weather reduces the incoming solar radiation and inhibits photochemical processes. The mean annual insolation for Santos is 1,376 h with 70% of cloud coverage.…”
mentioning
confidence: 94%
“…Also the few existing measurement data points indicated a spatial homogeneity, with mean values just above 2 µg m -3 at the sites MD roof and SC reported in this paper and also at the 5 university campus, considering the year-long dataset from 2014-2015 (Polezer et al, 2018). Within street canyons, the BC levels were locally raised (Johansson et al, 2017;Krecl et al, 2016) and also close to highways with diesel traffic (Andrade et al, 2012). Even if BC levels show to be spatially homogenous in the urban background, there were large temporal variations due to meteorological conditions, changes in the long-range contribution and likely due to some unidentified BC sources inside or just outside the city.…”
Section: Discussionmentioning
confidence: 99%